Proteomic analysis of leaves and roots during drought stress and recovery in Setaria italica L. - Gao, Hui; Ge, Weina; Bai, Lin; Zhang, Ting; Zhao, Ling; Li, Jingshi; Shen, Jiangjie; Xu, Ningwei; Zhang, Haoshan; Wang, Genping; Lin, Xiaohu (Frontiers in Plant Science, 2023)
Drought is a major environmental factor that limits agricultural crop productivity and threatens food security. Foxtail millet is a model crop with excellent abiotic stress tolerance and is consequently an important subject for obtaining a better understanding of the molecular mechanisms underlying plant responses to drought and recovery. Here, the physiological and proteomic responses of foxtail millet (cultivar Yugu1) leaves and roots to drought treatments and recovery were evaluated. Drought-treated foxtail millet exhibited increased relative electrolyte leakage and decreased relative water content and chlorophyll content compared to control and rewatering plants. A global analysis of protein profiles This is a provisional file, not the final typeset article was evaluated for drought-treated and recovery-treatment leaves and roots. We also identified differentially abundant proteins in drought and recovery groups, enabling comparisons between leaf and root tissue responses to the conditions. Principal component analysis suggested a clear distinction between leaf and root proteomes for the drought and recovery treatment plants. Gene Ontology enrichment and co-expression analyses indicated that the biological responses of leaves differed from those in roots after drought and drought recovery. These results provide new insights and data resources for investigating the molecular basis of tissue-specific functional responses of foxtail millet during drought and recovery, thereby significantly informing crop breeding.